ANALISIS RASIO LIKUIDITAS DAN RENTABILITAS PADA KINERJA KEUANGAN PERUSAHAAN - Khotijah, Siti; Mulyati, Awin; Pratiwi, Ni Made Ida (Jurnal Dinamika Administrasi Bisnis, 2019)
This Study was aimed to know the level of cororate financial performance during a certain period. By using financial ratios analysis (Liquidity Ratio and Profitability Ratio) of a company and the concept of Economic Value Added (EVA). The problems discussed in this study is how Ratio Analysis can measure the financial performance of PT. Surabay Industrial Estate Rungkut (SIER) company for the period 2015 – 2017.The type used is case study. Data used is documentation and analytical technique is financial ratio analysis. The population of this study is the company’s financial statements for the period 2015 – 2017. Data collection techniques are done with literature studies and field studies. Data collection techniques are done by financial Ratio Analysis.The results of this study show that PT. Surabaya Industrial Estate Rungkut (SIER) is better Ratio and almost all Ratios show good Ratio Results.The results of this study are PT. Surabaya Industrial Esatate Rungkut (SIER) and company performance can be measured by using measuring instrument is called EVA ( Economic Value Added). By using the calculation method in financial statement Analysis and company performance, the results of PT. SIER’s company performance are optimal and able to exprince increased profit significantly.